Representation of chemical structures - Engel, Thomas (Henry Stewart Talks, 2011)
Nomenclature, Structure diagrams, Linear notations (SMILES, SLN, InChi), Graph theory, Matrix representation, Connection table, Canonicalization, Markush structures, Fragment coding, Fingerprints, Hashcode
Reviewed at 2022/04/12